RADON DISTRIBUTION IN GROUNDWATER OF TAIWAN - Han Y.L.; Tom kuo M.C.; Fan K.C.; Chiang C.J.; Lee Y.P. (My University, 2006)
Radon levels were surveyed in 517 monitoring wells constructed in five major groundwater areas of Taiwan. The radon concentration in groundwater samples varied in a wide range from below the detection limit of 18 pCi/L up to 1,100 pCi/L. A worldwide comparison of reported groundwater radon levels was conducted. Overall radon levels in Taiwan groundwater are relatively low compared to other countries because the geology of Taiwan is mainly comprised of sedimentary rocks. Among the 517 wells monitored, only five wells were found with radon concentrations higher than 500 pCi/L. These five wells are all located near the Chaochou Fault in the Pingtung Plain. This study suggests that well sites near the Chaochou Fault could be good locations to monitor radon anomalies for earthquake prediction and should be avoided for developing domestic water supply. In the recharge area near the Chaochou Fault, the radon concentration in groundwater from shallow wells was approximately 1/2 to 1/4 of that from deep wells in the same cluster.
Keywords: RADON-222; FAULT; GROUNDWATER RECHARGE